Mechanisms of Ijara instruments as an innovation for sustainable development - Yahi, Mohamedelamine; Boudkhil, Mohamedelamine (Finance and Business Economies Review, 2020)
This study aims to highlight the mechanisms of the Ijara instruments as a tool for activating sustainable development through knowledge of the methods of work of these certificates, which was able to find a foothold in the capital market, and played a major role in providing liquidity during the depletion of many projects, By promoting sustainable development that has brought about positive changes at the social, environmental and economic levels.